The concept of sustainable business location: preliminary study on purpose-built office in Malaysia - Heng, Jia Yun; Mohd Safian, Edie Ezwan; Ramin, Ahmad Kaseri (JARDCS, 2018)
In Malaysia, purpose-built office (PBO) market has shown positive developments. Yet, every property had its own locational characteristics, including PBO. Location of PBO is the specific consideration for commercial property market participants to meet their needs within the best available option at different decision making levels. Hence, locational characteristics of PBO affects the investment decision made by stakeholders. Sustainable concept has emerged in urban design and planning of PBO. The aim of this paper is to identify the characteristics of sustainable business location for PBO in Malaysia. In order to achieve this purpose, sustainable business location characteristics of PBO will be reviewed and discussed in a global and local context to provide a better understanding of importance of locational criteria of PBO in a comprehensive way. As a result, characteristics of sustainable business location framework of PBO in Malaysia will be identified and used as the variables that need to be considered in location decisions. Thus, combining Analytic Network Process (ANP) and Geographic Information System (GIS) will consider the physical as well as the non-physical characteristics of PBO in term of sustainable business location.